Historical and projected climate data for natural resource management in western Canada - Mbogga, Michael S.; Hamann, Andreas; Wang, Tongli (Agricultural and forest meteorology, 2009)
In this paper we present a comprehensive set of interpolated climate data for western Canada, including monthly data for the last century (1901–2006), future projections from general circulation models (68 scenario implementations from 5 GCMs), as well as decadal averages and multiple climate normals for the last century. For each of these time periods, we provide a large set of basic and derived biologically relevant climate variables, such as growing and chilling degree days, growing season length descriptors, frost free days, extreme minimum temperatures, etc. To balance file size versus accuracy for these approximately 15,000 climate surfaces, we provide a stand-alone software solution that adds or subtracts historical data and future projections as medium resolution anomalies (deviations) from the high resolution 1961–1990 baseline normal dataset. For a relative quality comparison between the original normal data generated with the Parameter Regression of Independent Slopes Model (PRISM) and derived historical data, we calculated the amount of variance explained (R2) in original weather station data for each year and month from 1901 to 2006. R2 values remained very high for most of the time period covered for most variables. Reduction in data quality was found for individual months (as opposed to annual, decadal or 30-year climate averages) and for the early decades of the last century. We discuss the limitations of the database and provide an overview of recent climate trends for western Canada.
Keywords: Climate normals; Historical climate data; PRISM; Interpolation